Comparison of head impact frequency and magnitude in youth tackle football and ice hockey. Issue 8 (11th June 2022) - Meliambro, Julia; Karton, Clara; Cournoyer, Janie; Post, Andrew; Hoshizaki, T. Blaine; Gilchrist, Michael D.
Abstract: Repetitive head impacts are a growing concern for youth and adolescent contact sport athletes as they have been linked to long term negative brain health outcomes. Of all contact sports, tackle football and ice hockey have been reported to have the highest incidence of head or brain injury however, each sporting environment is unique with distinct rules and regulations regarding contact and collisions. The purpose of this research was to measure and compare the head impact frequency and estimated magnitude of brain tissue strain, amongst youth tackle football and ice hockey players during game play. Head impact frequency was documented by video analysis of youth tackle football and ice hockey game play. Impact magnitude was determined through physical laboratory reconstructions and finite element modelling to estimate brain tissue strains. Tackle football demonstrated significantly higher impact frequency (P < 0.01) and magnitude of estimated brain tissue strains (P < 0.01) compared to ice hockey. A significantly higher number of higher strain head impacts were documented in tackle football when compared to ice hockey (P < 0.01). These differences suggest that youth football players may experience increased frequency and magnitude of estimated brain tissue strains in comparison to youth hockey.